Pustaha Laklak: Antara Karya Satra dan Souvenir - Churmatin Nasoichah (Balai Arkeologi Sumatera Utara, 2009)
AbstractPustaha Laklak is the literary of Batak society. It’s needed to improve the idea to create and perpetuate it. To promote, pustaha laklak could be used as souvenir although it’s not the original one.